A estética feminina como atributo de exclusão no mercado de trabalho brasileiro (Management and Connections Journal, 2024)
Sexism and racism are the most perverse ideologies in relation to gender and race issues in Brazilian society. Women, especially black women, are discriminated against from birth and remain so throughout their lives because of their phenotype. The objective of the study is to identify how the aesthetic profile constitutes an obstacle to insertion in the Brazilian labor market. The theoretical approach was the Hasenbalg paradigm and the Technology of Self. A descriptive, qualitative research was carried out with twenty-two black and white students. Discourse analysis was performed to analyze the narratives. The results show that discrimination in selection goes beyond racial prejudice, as it includes aesthetic issues that lead to women's illness.
Keywords: job market; racism; black women; sexism; aesthetic; Technology of self